2004
DOI: 10.1016/j.ijpsycho.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of brain oscillations as functional correlates of cognitive systems: a study of frontal inhibitory control in alcoholism

Abstract: Event-related oscillations play a key role in understanding the brain dynamics and human information processing. In the present study, the Go/No-Go paradigm has been used to examine whether alcoholics have poor inhibitory control as compared to control subjects in terms of different oscillatory brain responses. The matching pursuit algorithm was used to decompose the event-related electroencephalogram into oscillations of different frequencies. It was found that alcoholics (n=58) showed significant reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
153
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 236 publications
(245 reference statements)
18
153
2
Order By: Relevance
“…In our previous study in alcoholics (Kamarajan et al 2004), we demonstrated that alcoholics had lower delta and theta activity in the NoGo condition, and reduced delta activity in the Go condition. In the present study, the OA subjects who are at high risk to develop alcoholism manifest these deficits in EROs and additionally manifest decreased theta activity in the Go condition, and markedly reduced activity in the theta and alpha1 bands in the NoGo condition.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In our previous study in alcoholics (Kamarajan et al 2004), we demonstrated that alcoholics had lower delta and theta activity in the NoGo condition, and reduced delta activity in the Go condition. In the present study, the OA subjects who are at high risk to develop alcoholism manifest these deficits in EROs and additionally manifest decreased theta activity in the Go condition, and markedly reduced activity in the theta and alpha1 bands in the NoGo condition.…”
Section: Discussionmentioning
confidence: 58%
“…Recently, we showed that alcoholics have deficient delta and theta oscillatory responses during the NoGo condition in a Go/NoGo task (Kamarajan et al 2004). Further, decreased NoGo-P3 amplitude has also been reported in alcoholics (Cohen et al 1997a;Kamarajan et al, 2005b) as well as in children of alcoholics (Cohen et al 1997b;Kamarajan et al, 2005a).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations